Alcoholic beverage from candy scrap - Cruz, Ma. Cristina M. (1978)
The study was undertaken to develop an alcoholic beverage from candy scrap. This study included the determination of a favorable specie of Saccharomyces, S. cerevisiae or S. champagne based on their alcohol-producing ability and the effect of urea (0.1% and 0.2%) on the rate of fermentation and production of alcohol. The "syruped" method of fermentation was employed wherein "sugar solution" was added at specified intervals to a fermentable liquid containing 16% total soluble solids. Results showed that S. cerevisiae had a better alcohol-producing ability than S. champagne. The alcoholic beverage inoculated with S. cerevisiae had an alcohol content of 0.50% while the beverage inoculated with S. champagne had an alcohol content of only 0.35%. Objective and subjective tests indicated that the alcoholic beverage with 0.2% urea had a faster rate of fermentation as shown from the decrease in the % soluble solids readings taken at daily intervals, and higher alcohol yield than the fermentable liquid with only 0.1% urea. The former had % alcohol content of 1.57% while the latter had 0.94% alcohol content.